Kompetensi Petani Unggul dalam Membentuk Capacity Building Pertanian Sayuran Dataran Tinggi di Sumatera - Raysah Yunita Rahma; Muhammad Syamsun; Anggraini Sukmawati (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2014)
The agricultural potential in Indonesia still becomes the excellence because Indonesia is the agrarian country. The role of agricultural sector in the national economy is empirically proven to be real enough both in quite normal economy and when the economy facing the crisis. This is seen from two important indicators i.e. the contribution to the sector of Gross Domestic Product (GDP), and the labor absorption that always dominates in the agricultural field.This is caused by the lack of competence of farmer to be able to develop in the agricultural sector. With this is needed the farmer competence in forming the farming capacity building so the farmer can play the role in the community and can compete in the current globalization era. Based on the above problem, the research aims to: (1) analyze how the competence is owned by the farmer in Sumatera, (2) obtain the picture of farmer superior competence model in Sumatera to form the capacity building of highland vegetable farmer, and (3) give any solution which should be done in order to be able to increase the farmer competence in Sumatera. In this research, for analyzing the farmer superior competence and the making of superior competence model in forming the capacity building of highland vegetable farming in Karo District, it is used the ISM, AHP, and IPA.